Entrepreneurship in the Cultural Industries in Southeast Asia - Tran, Huyen Trang; Pichanič, Mikuláš, 1942-; Pulkrábková, Jana; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2015)
The aim of this thesis is to introduce to whomever it may concern the new socio-economical phenomenon Korea has brought to the global creative industry. The term Hallyu will be clarified in all its details and after understanding the whole meaning behind it, the reader will be fully aware of all circumstances concerning the main topic of this thesis -- K-pop. The Korean entertainment industry is already very unique as it is on its own, but it is even more worth looking at when comparing to the global music industry in general. A thorough inside look into K-pop's globalization strategy, its venture-like approach of the creative industry as well as curiosities and confrontational issues around it will be explained in here.
Vedoucí práce: Mikuláš Pichanič
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor bakal. práce]; bakalářské práce; bachelor's theses